Performance and migration. - Cox, Emma ([S.l.] : Routledge, 2021)
This third volume in the 4x45 series addresses some of the most current and urgent performance work in contemporary theatre practice. As people from all backgrounds and cultures criss-cross the globe with an ever-growing series of pushes and pulls guiding their movements, this book explores contemporary artists who have responded to various forms of migration in their theatre, performance and multimedia work. The volume comprises two lectures and two curated conversations with theatre-makers and artists. Danish scholar of contemporary visual culture, Anne Ring Petersen, brings artistic and political aspects of postmigration' to the fore in an essay on the innovations of Shermin Langhoff at Berlin's Ballhaus Naunynstrae, and the decolonial work of Danish-Trinidadian artist Jeannette Ehlers. The racialised and gendered exclusions associated with navigating the industry' for non-white female and non-white non-binary artists are interrogated in Melbourne-based theatre scholar Paul Rae's interview with two Australian performers of Indian heritage, Sonya Suares and Raina Peterson. UK playwrights Joe Murphy and Joe Robertson of Good Chance Theatre discuss their work in dialogue, and with their colleague, Iranian animator and illustrator Majid Adin. Emma Cox's essay on Irish artist Richard Mosse's video installation, Incoming, discusses thermographic heat signatures' as ameans of seeing migrants and the imperative of envisioning global climate change. An accessible and forward-thinking exploration of one of contemporary performance's most pressing influences, 4x45 Performance and Migration is a unique resource for scholars, students and practitioners of Theatre Studies, Performance Studies and Human Geography.
Keywords: Arts and society; Theater and society; Emigration and immigration in art; Performing arts -- Themes, motives; PERFORMING ARTS / General; SOCIAL SCIENCE / Human Geography; SOCIAL SCIENCE / Anthropology / Cultural